HUBUNGAN PENGETAHUAN TENTANG KODE ETIK KEDOKTERAN DENGAN SIKAP DOKTER TERHADAP PEMBERIAN RESEP OBAT ATAS PENGARUH PERUSAHAAN FARMASI - Yunisa Dwi Kurniawati, (2022)
Violations of medical ethics that occur in Indonesia seem to have become a natural thing. In fact, many doctors sign contracts with large pharmaceutical companies and receive monetary or material rewards. Apart from being financial, sometimes the risks of using prescribed drugs outweigh the benefits and become irrational. In daily practice, many drugs are used inappropriately and widely, ranging from prescriptions without indications, inappropriate management, prescribing expensive drugs or uncertain benefits, to the practice of various kinds of drugs. This research is an analytic observational with a cross-sectional approach. The sample used was 94 members of the IDI South Jakarta Branch and the sample was taken using a simple random sampling technique. Univariate analysis showed that the majority of the samples were female, aged 24-30 years, had a good level of knowledge and high attitudes. Bivariate analysis using the Chi-Square test showed that there was no significant correlation between knowledge of the medical code of ethics and the attitude of doctors towards drug prescribing due to the influence of pharmaceutical companies (p = 0.384). The conclusion is that most members of IDI South Jakarta have a good level of knowledge, high attitudes, and there is no correlation between knowledge of the Medical Code of Ethics and the attitudes of IDI members in the South Jakarta area towards drug prescribing due to the influence of pharmaceutical companies. One of the factors that gives rise to the opportunity for gratification between doctors and pharmaceutical companies is P2KB. The P2KB program is an opportunity for pharmaceutical companies to sponsor doctors by sponsoring registration fees, accommodation, travel, and even holding a free medical symposium attended by all doctors in Indonesia.